The Antillean genus Pogrima Schaus, 1940 (Lepidoptera: Pyralidae, Galleriinae) - Vitor O. Becker (SHILAP)
Pogrima Schaus, 1940 is represented by three species: P. palmasalis Schaus, 1940, from Cuba, Puerto Rico and the Lesser Antilles, P. borinqualis Becker, sp. nov., from Puerto Rico, and P. tainalis Becker, sp. nov., from Cuba.